RESPIRATORY DISEASES RELATED TO PRACTICE EXERCISE OUTDOORS (Fiep Bulletin - online, 2017)
This article aims to investigate the causes of the major diseases related to the practice of outdoors exercises andphysical activities. We have checked which are the main diseases and also the relapses, seeking to clarify the impacts to physicalperformance. We have rewies scientific literature and reliable database.